Importance of the Spatial Distribution of Rare Earth Elements in the Bottom Sediments of Reservoirs as a Potential Proxy for Tracing Sediments Sources. - Fonseca, Rita (2021)
The geochemical composition of rare earth elements (REE) in the bottom sediments of two Do-minican reservoirs and in soils from their catchments was studied to identify possible sources of the deposited materials. Knowledge of the origin of the sediments will serve to control the ex-cessive rates of erosion and sedimentation that occur annually due to periodic extreme climatic events that promote excessive silting of the lakes, followed by loss of storage capacity and deg-radation of water quality. The REE contents of sediments and soils were normalized to the North American Shale Composite (NASC) and the ratio of light/heavy rare earths (LREE/HREE ratio), Ce and Eu anomalies, and some fractionation parameters were determined. The REE patterns are more homogeneous in the sediments, indicating uniform sedimentation in both deposits. The sediment data reflect depletion of REE from the sources, enrichment of light REE (LREE) and some middle REE (MREE), and positive Eu and Ce anomalies. All data were plotted in correlation diagrams between some fractionation parameters of light–middle–heavy REE and anomalies of Ce and Eu. The similarity of the ratios between these parameters in all samples and the overlap of data from soils and rocks on the sediment projection in the diagrams allowed a good discrimina-tion of the main sources of the materials.